Adsorption and coadsorption mechanisms of Cr(VI) and organic contaminants on H3PO4 treated biochar. (November 2017) - Zhao, Nan; Zhao, Chuanfang; Lv, Yizhong; Zhang, Weifang; Du, Yuguo; Hao, Zhengping; Zhang, Jing
Abstract: The study of simultaneous removal of heavy metals and organic contaminants has practical applications due to the coexistence of complex pollutants in the wastewater or soil. In this work, biochar was prepared to study the removal efficiencies of Cr(VI), naphthalene (NAP) and bisphenol A (BPA) in the single or mixed systems. H3 PO4 -treated biochar presented a much higher adsorption capacity of the pollutants than the untreated biochar and also showed a high resistance to coexisting salts. The maximum adsorption capacities for Cr(VI) and BPA were 116.28 mg g −1 and 476.19 mg g −1, respectively. Coadsorption experiments revealed that the presence of organic pollutants caused a limited decrease (∼10%) of removal efficiency of Cr(VI) and no further decrease was observed with higher concentrations of organic pollutants, while the presence of Cr(VI) had little impact on the removal of NAP. Infrared spectra and molecular simulation demonstrated that Cr(VI) was mainly adsorbed on the biochar via chemical complexation, while the organic pollutants through π-π interaction. Unexpectedly, the addition of Cr(VI) increased the removal efficiency of BPA, probably due to the increased H-bond interactions between BPA and the biochar through bridge bonds of oxygenic groups from CrO4 2− . Highlights: H3 PO4 treated biochar has much higher adsorption capacities than the untreated one. H3 PO4 treated biochar can remove Cr(VI) and NAP (or BPA) simultaneously. The presence of Cr(VI) can increase the removal efficiency of BPA. Organic pollutants caused a limited decrease of removal efficiency of Cr(VI). High ionic strength does not affect removal efficiencies of Cr(VI), NAP and BPA.